Posted by
**Valerie** on
.

Can someone please help me do this problem? That would be great!

Simplify the expression:

sin theta + cos theta * cot theta

I'll use A for theta.

Cot A = sin A / cos A

Therefore:

sin A + (cos A * sin A / cos A) =

sin A + sin A =

2 sin A

I hope this will help.

in my algebra book, it says that Cot A=cos A/sin A, not sin A/cos A

That changes things a bit, doesn't it?

cot A = cos A / sin A

sin^2 A + cos^2 A = 1

Therefore:

sin A + (cos A * cos A / sin A) =

sin A + (cos^2A / sin A) =

Using sin A as a common denominator:

(sin^2 A / sin A) + (cos^2 A / sin A) =

(sin^2 A + cos^2 A) / sin A =

1 / sin A

Sorry for the error.

thank you!!